Zooplankton abundance and distribution along the Mawson coast, East Antarctica - Weldrick, Christine K.; Brasier, Madeleine J.; Burns, Alicia; Johnson, Olivia J.; Maschette, Dale (Frontiers in Marine Science, 2024)
During the summer of 2021, we conducted a comprehensive study on zooplankton communities along East Antarctica (55°E to 80°E) as part of the Trends in Euphausiids off Mawson, Predators, and Oceanography (TEMPO) survey program. Hierarchical agglomerative clustering identified three distinct zooplankton clusters based on environmental factors. Seven potential indicator taxa associated with specific clusters include copepods, pteropods, amphipods, and euphausiids. Mainly consisting of small copepods, chaetognaths and foraminifera, Cluster 1 (n = 34) was characterized by the highest abundance (74,386 ind./1000 m3), spanning wide latitudinal and longitudinal gradients, deeper waters (mean depth = 3,475 m ± 739 m), and higher chlorophyll-a concentrations (mean = 49.13 mg m−2 ± 24.38 mg m−2). Cluster 2 (n = 4) featured the lowest abundance (1,059 ind./1000 m3) and the fewest sampling stations along the narrowest latitudinal range. Copepods, euphausiids, and foraminifera were among the most abundant in this group. Cluster 3 (n = 10), located near the ice edge, displayed a distinct temperature range (−1.46°C to 1.18°C) and moderate zooplankton abundance (22,629 ind./1000 m3) consisting of copepods, euphausiids, and ostracods. IndVal analysis identified seven species as indicators of environmental conditions and Generalized Additive Models (GAMs) were used to model their abundance, as well as total zooplankton abundance. Across all models, significant drivers included chlorophyll-a, temperature, number of days since sea ice melt and mixed layer depth. The model for total zooplankton abundance explained 70.9% of the deviance, with number of days since ice melt and chlorophyll-a concentration emerging as the strongest predictors. These findings provide crucial insights into the ecological implications of changing climate conditions on East Antarctica zooplankton communities and their potential repercussions on the broader Southern Ocean ecosystem. This research enhances our understanding of the intricate relationship between environmental shifts and Southern Ocean ecology.